Nichilismo e pensiero tragico - Givone, Sergio (Bollettino Filosofico, 2015)
The paper focuses on Parmenide’s necessary “being” and on the fundamental ontology derived from it. The aim is to show that this ontology is not based on the oblivion of the being, but on the power of negation’s oblivion. This power of negation is essential to think the being; otherwise, being can be thought of only as necessity, as impossibility of not being.